PERAN KEPEMIMPINAN ETIS DAN PEMBERDAYAAN PSIKOLOGI TERHADAP KEPUASAN UNTUK MENIINGKATKAN KINERJA ATLET PPLP SULAWESI TENGGARA - Harmoko .; Heru Sulistyo (Jurnal Ekonomi dan Bisnis, 2014)
The purpose of this study is to examine and obtain empirical evidence of a significant effect of ethical leadership and psychological empowerment on satisfaction PPLP athletes Southeast Sulawesi , to examine and obtain empirical evidence of the significance of the influence of ethical leadership and psychological empowerment on the performance of athletes PPLP Southeast Sulawesi and to find the significance of the effect of satisfaction work on the performance of athletes PPLP Southeast Sulawesi . Problems in the lift in this study were 1 ) How does the performance athlete Ethical Leadership Southeast Sulawesi PPLP 2 ) How PsychologicalEmpowerment influence on performance ( achievement ) Athletes PPLP Southeast Sulawesi 3 ) How does Ethical Leadership on Job Satisfaction Athletes PPLP Southeast Sulawesi 4 ) how to influence Psychology Empowerment on Job Satisfaction Athletes PPLP Southeast Sulawesi 5 ) how does Job Satisfaction to Performance ( achievement ) Athletes PPLP Southeast Sulawesi.The research was conducted on athletes PPLP Southeast Sulawesi . Data was collected by questionnaire and literature with a number sampel to many 90 respondents consisting of 11 female respondents and 79 male respondents . The data analysis technique used is the Patrial Least Square (PLS) analysis is a powerful metoode therefore does not assume the data to be certain scale data, not need many assumptions and sample size should not be large . The results showed that ethical leadership variable had no significant effect on performance , psychologicalempowerment have a significant effect on performance , ethical leadership significant effect on satisfaction, psychological empowerment significant effect on satisfaction, and satisfaction have a significant effect on performance.Keywords : Ethical Leadership, Phsycological Empowertment, Satisfaction and Performance.